Selectivity of Herbicides in Controlling Weeds in Corn (Zea mays L) With A Tegel and Jajar Legowo Planting Pattern in West Aceh Regency - Fakhrurrazi, Fakhrurrazi; Baidhawi, Baidhawi; Yusra, Yusra (International Journal of Engineering, Science and Information Technology, 2024)
Maize (Zea mays L.) has a strategic role in meeting global food needs. How is the selectivity of herbicides in cultivation patterns 1 (single rows) and 2 (double rows) in Maize plants (Zea Mays L), how is the combination of herbs and plant pattern suitable for the management of weeds in corn crops (Zea mays L), how are the interactions of selectivities of herbicides and cultivation of maize (Zea mays L). This study uses Random Group Design (RGD) factorial patterns where factor 1 (herbicide) and factor 2 (planting pattern). The herbicide is composed of 4 types: H0 (control), H1 (Atrazine 180g/l + Mesotrione 40g/ l + Nicosulfuron 20 g/l, H2 (Atazine 500g/L, Mesotrione 50 g/L) and H3 (Topramezone 10 g/ L + Atrazine 300 g/ l). While the planting pattern consists of 2 types: P1: single row (70 x 20 cm) and P2: double rows (100x20x40 cm). Some conclusions were obtained, among others: The use of the herbicide atrazine in several formulas within the tile and legowo planting patterns does not cause poisoning in corn plants. The combination of herbicides (Topramezon 10 g/l and Atrazine 300 g/l / Tile) is most suitable for corn plants. There is an interaction between the herbicide and the planting pattern on the parameters of ear weight without husk and ear length without husk, which shows significant differences